Uji Variasi Tekanan Nosel Terhadap Karakteristik Semprotan Bahan Bakar Biodiesel - I Wayan Suma Wibawa; I Gusti Bagus Wijaya Kusuma; I Nyoman Budiarsa (Jurnal Mettek: Jurnal Ilmiah Nasional dalam Bidang Ilmu Teknik Mesin, 2015)
In the middle of the thinness of the availability of fossil fuels, making researchers from various countries are aggressively seeking alternative energy sources that can be renewed, one of which is biodiesel from callophyluminophylum. Callophyluminophylum use of biodiesel in diesel engines still experiencing problems, due to the viscosity and density higher than petroleum diesel it results in the performance of the diesel engine is not optimal. One solution to overcome the above problems is to put more pressure on the injector so that the spray is more subtle, then tested the effect of pressure injector / nozzle of the spray characteristics. The variations in the pressure nozzle 90 bar, 100 bar, 110 bar, 120 bar and 130 bar (range working pressure nozzle from the factory) using petroleum diesel (100%), callophyluminophylum biodiesel 100% and callophyluminophylum biodiesel 5% + petroleum diesel 95 %. Fuel spray characteristics test in the penetration of the spray tip length (L), spray rate (v or Uin), spray angle (?), and distribution of large granules are formed on each - each variation of pressure. From the testing that was done then get the following, at a pressure of 120 bar nozzle BD 5% has characteristics that most closely D 100% (petroleum diesel) both of the speed of the spray, spray angle and the amount of the grain. Key words: Pressure nozzle, the length of the spray, spray time, spray angle, the distribution of grain.